Raman Spectroscopic Measurements of Dermal Carotenoids in Breast Cancer Operated Patients Provide Evidence for the Positive Impact of a Dietary Regimen Rich in Fruit and Vegetables on Body Oxidative Stress and BC Prognostic Anthropometric Parameters: A Five-Year Study. (26th April 2016) - Perrone, A.; Pintaudi, A. M.; Traina, A.; Carruba, G.; Attanzio, A.; Gentile, C.; Tesoriere, L.; Livrea, M. A.
Abstract : Dermal carotenoids are a feasible marker of the body antioxidative network and may reveal a moderate to severe imbalance of the redox status, thereby providing indication of individual oxidative stress. In this work noninvasive Resonance Raman Spectroscopy (RRS) measurements of skin carotenoids (skin carotenoid score (SCS)) were used to provide indications of individual oxidative stress, each year for five years, in 71 breast cancer (BC) patients at high risk of recurrence. Patients' SCS has been correlated with parameters relevant to BC risk, waist circumference (WC), and body mass index (BMI), in the aim of monitoring the effect of a dietary regimen intended to positively affect BC risk factors. The RRS methodological approach in BC patients appeared from positive correlation between patients' SCS and blood level of lycopene. The level of skin carotenoids was inversely correlated with the patients' WC and BMI. At the end of the 5 y observation BC patients exhibited a significant reduction of WC and BMI and increase of SCS, when strictly adhering to the dietary regimen. In conclusion, noninvasive measurements of skin carotenoids can (i) reveal an oxidative stress condition correlated with parameters of BC risk and (ii) monitor dietary-related variations in BC patients.